Implementasi SWOT dalam Meningkatkan Daya Saing pada UMKM Perdana Semarang - Widiyanti Widiyanti; Ratna Tunjungsari; Agung Budiartono; Agus Prasetyo (Lembaga Pengembangan Kinerja Dosen, 2025)
Mapping a business using SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) is not only essential as an initial step before starting a business but also crucial when developing an existing business to ensure its sustainability. MSMEs operating in a competitive market must be able to adapt and respond to market and technological changes. This study was conducted through mentoring and training for MSMEs in Perdana Semarang on implementing SWOT analysis to enhance their competitiveness. The activity aims to provide an understanding of the importance of SWOT analysis for MSMEs and to teach how to map a SWOT matrix for their business. In practice, participants were involved in identifying relevant strengths, weaknesses, opportunities, and threats, analyzing these factors, and mapping appropriate strategies. The implementation of adaptation to changes was done by developing products and services, innovating better than competitors, creatively seeking capital, expanding business networks, and gaining support from various parties. SWOT analysis serves as a method to identify and analyze internal and external factors affecting a business, helping businesses prepare for uncertain market conditions.